Seasonal reproductive costs contribute to reduced survival of female greater sage‐grouse. (11th December 2012) - Blomberg, Erik J.; Sedinger, James S.; Nonne, Daniel V.; Atamian, Michael T.
<x xml:space="preserve">Abstract</x> Tradeoffs among demographic traits are a central component of life history theory. We investigated tradeoffs between reproductive effort and survival in female greater sage‐grouse breeding in the American Great Basin, while also considering reproductive heterogeneity by examining covariance among current and future reproductive success. We analyzed survival and reproductive histories from 328 individual female greater sage‐grouse captured between 2003 and 2011, and examined the effect of reproductive effort on survival and future reproduction. Monthly survival of females was variable within years, and this within‐year variation was associated with distinct biological seasons. Monthly survival was greatest during the winter (November–March; ΦW= 0.99 ± 0.001 SE), and summer (June–July; ΦS= 0.98 ± 0.01 SE), and lower during nesting (April–May; ΦN= 0.93 ± 0.02 SE) and fall (August–October; ΦF= 0.92 ± 0.02 SE). Successful reproduction was associated with reduced monthly survival during summer and fall, and this effect was greatest during fall. Females that successfully fledged chicks had lower annual survival (0.47 ± 0.05 SE) than females who were not successful (0.64 ± 0.04 SE). Annual survival did not vary across years, consistent with a slow‐paced life history strategy in greater sage‐grouse. In contrast, reproductive success varied widely, and was positively correlated with annual rainfall. We found evidence for heterogeneity among females with respect to reproductive success; compared with unsuccessful females, females that raised a brood successfully in year t were more than twice as likely to be successful in year t+ 1. Female greater sage‐grouse incur costs to survival associated with reproduction, however, variation in quality among females may override costs to subsequent reproductive output.